Effects of forest bathing (Shinrin-yoku) in stressed people - Queirolo, Luca; Fazia, Teresa; Roccon, Andrea; Pistollato, Elisa; Gatti, Luigi; Bernardinelli, Luisa; Zanette, Gastone; Berrino, Franco (Frontiers in Psychology, 2024)
Aim This study aims to explore the physiological effect of forest bathing on stress management. Methods A total of 29 volunteers participated in this pre-post design, which lacked a control group. Several physiological parameters were recorded, including heart rate (HR), heart rate variability (HRV), electrodermal activity (EDA), blood pressure (BP), immunoglobulin A (IGA), and salivary cortisol (sCort). Additionally, the Perceived Stress Scale (PSS-10) was administered before forest exposure. Measurements were taken before and after participants spent 2 days fully immersed in a forest environment. To further assess stress management, participants completed a Mental Arithmetic Task (MAT) before and after forest immersion, during which EDA, HRV, and HR were monitored using an Empatica E4 wristband. Measurements were taken at baseline, during MAT, and afterward (recovery). Results Participants exhibited moderate perceived stress levels before forest immersion (mean PSS-10 = 21.22, SD = 3.78). Post-forest exposure, there was a significant decrease in sCort (p < 0.05) and EDA (p < 0.001), while HRV increased (p < 0.001), and diastolic blood pressure rose (p < 0.05). ANOVA results from the MAT showed a significant increase in parasympathetic activity across all conditions post-immersion (p < 0.05), except during recovery, while EDA decreased in all conditions post-forest exposure (p < 0.05). Conclusion Shinrin-yoku significantly improved stress management at a physiological level and could be a valuable intervention for individuals experiencing stress. However, longitudinal studies with a control group are necessary to determine whether these effects are sustained over time. Nonetheless, this study highlights the potential benefits of forest immersion for stress reduction by enhancing sympathovagal balance and the adaptability of the stress response system.